1993
DOI: 10.1021/jm00067a020
|View full text |Cite
|
Sign up to set email alerts
|

Synthesis and antitumor activity of 10-propargyl-10-deazaaminopterin

Abstract: Successive alkylation of dimethyl homoterephthalate with propargyl bromide and 2,4-diamino-6-(bromomethyl)pteridine followed by ester saponification at room temperature afforded 2,4-diamino-4-deoxy-10-carboxy-10-propargyl-10-deazapteroic acid. The 10-COOH was readily decarboxylated by heating in DMSO at a temperature of only 120 degrees C to yield the diamino-10-propargyl-10-deazapteroic acid intermediate. Coupling with diethyl L-glutamate and ester hydrolysis gave the title compound. The 10-propargyl analogue… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

2
39
0

Year Published

1994
1994
2022
2022

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 62 publications
(41 citation statements)
references
References 2 publications
2
39
0
Order By: Relevance
“…1). Pralatrexate was rationally designed to have high affinity for the RFC and folylpolyglutamate synthase (FPGS), leading to enhanced and selective intracellular internalization and retention in tumor cells (5). RFC is an oncofetal protein known to be highly expressed in embryonic and malignant tissues (6,7).…”
Section: Pharmacologymentioning
confidence: 99%
“…1). Pralatrexate was rationally designed to have high affinity for the RFC and folylpolyglutamate synthase (FPGS), leading to enhanced and selective intracellular internalization and retention in tumor cells (5). RFC is an oncofetal protein known to be highly expressed in embryonic and malignant tissues (6,7).…”
Section: Pharmacologymentioning
confidence: 99%
“…It is approximately 5 fold more potent than MTX as an inhibitor of L1210 cells [184]. A phase I study defined a dose of 150 mg/m 2 given every 2 weeks as the recommended phase II dose [185].…”
Section: Pdxmentioning
confidence: 99%
“…In preclinical studies, pralatrexate has shown greater antitumor activity compared with methotrexate. 1 Human tumor xenograft studies in mice (including human breast cancer and human lung cancer xenografts) demonstrated improved regression of tumors with pralatrexate treatment, whereas methotrexate treatment resulted only in delayed tumor growth without a sustained regression at comparable doses. 2,3 Comparison of the efficacy of pralatrexate and methotrexate against several lymphoma cell lines (including diffuse large B-cell lymphoma, Burkitt lymphoma, transformed follicular lymphoma, T-cell lymphoma, and Hodgkin disease) showed a more than 10-fold increased in vitro cytotoxicity in pralatrexate-treated cells and improved regression of xenografts in nonobese diabetic/severe combined immunodeficiency mice.…”
mentioning
confidence: 99%